Effects of recently developed swimwear on drag during front crawl swimming - Ogita, F.; Huang, Z.; Kurobe, K.; Ozawa, G.; Taguchi, N.; Tanaka, T. (Biomechanics and Medicine in Swimming XI, 2010)
The effect on active drag of 3 new types of swimwear compared to conventional wear was investigated in 8 male subjects swimming at different velocities to establish the drag-velocity relationship. The active drag force was directly measured during front crawl swimming using a system of underwater push-off pads instrumented with a force transducer. When mean drag values were estimated for a range of swimming speed (1.2 to 1.8 m•s-1), statistically non-significant drag reduction effects of 1-5 N (2-6%) were observed for the new types of swimwear. Even if no major differences in drag were found among swimwear, our results suggest that the observed reduction, even if non significant, could indeed explain the observed competitive advantage.